The changing incidence of dengue fever in Hulu Langat, Selangor: a 5-year registry-based analysis - Ramli, Lina Farhana; Mohd Tohit, Nor Faiza; Salleh, Rosilawati; Suli, Zaliza (2019)
INTRODUCTION: Dengue fever, a mosquito-borne disease that occurs in tropical and subtropical areas of the world, is a significant threat for the mankind in both developing and developed countries. Dengue virus infection is a systemic disease and has dynamic change in clinical phase. This research aimed to study the epidemiology of dengue with reference to demographic profile, circulating serotypes and complications.